C.5 - "Ranchhoddas, Ratanlal" (Gurgaon, 2012)
This book contain the material on latest question in the law and competitive examination incorporated., to keep it concise, only important cases decided by the judiciary have been added. The Criminal Law (amendment) Act, 2013 has been substituted. These amendments have been incorporated in the book.
Keywords: Evidence